2014
DOI: 10.1002/dneu.22214
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptors on zebrafish Mauthner cells require CaMKII‐α for normal development

Abstract: Calcium/calmodulin dependent protein kinase 2 (CaMKII) is a multifunctional protein that is highly enriched in the synapse. It plays important roles in neuronal functions such as synaptic plasticity, synaptogenesis, and neural development. Gene duplication in zebrafish has resulted in the occurrence of seven CaMKII genes (camk2a, camk2b1, camk2b2, camk2g1, camk2g2, camk2d1, and camk2d2) that are developmentally expressed. In this study, we used single cell, real-time quantitative PCR to investigate the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 77 publications
(103 reference statements)
0
8
0
Order By: Relevance
“…The morphants show evidence of curved tails, cardiac edema and larger yolk sacs, while con-trol injected embryos appear to be morphologically and developmentally normal and are similar to uninjected clutch mates. Morphants experienced about 85-90% knockdown of targeted mRNA, as determined by quantification of cDNA copy number following quantitative real time PCR (Roy et al, 2014). We determined the efficacy of the morpholinos in this manner rather than by examining PCR gels for exon skipping because the Cacng2a morpholino is designed against an overlapping region between exon 1 and intron 1, which is 84 kB in size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphants show evidence of curved tails, cardiac edema and larger yolk sacs, while con-trol injected embryos appear to be morphologically and developmentally normal and are similar to uninjected clutch mates. Morphants experienced about 85-90% knockdown of targeted mRNA, as determined by quantification of cDNA copy number following quantitative real time PCR (Roy et al, 2014). We determined the efficacy of the morpholinos in this manner rather than by examining PCR gels for exon skipping because the Cacng2a morpholino is designed against an overlapping region between exon 1 and intron 1, which is 84 kB in size.…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish from the Oregon AB wild-type line were obtained from the University of Oregon and raised in the aquatics facility in the Department of Biological Sciences at the University of Alberta according to established protocols (Patten and Ali, 2007;Patten and Ali, 2009;Roy et al, 2014). Embryos were raised at 28.58C in Egg Water (60 lg mL 21 "Instant Ocean," United Pet Group, Cincinnati, OH) or Embryo Medium (mM: 13.7 NaCl; 0.54 KCl; 0.025 Na 2 HPO 4 ; 0.044 KH 2 PO 4 ; 1.3 CaCl 2 ; 1.0 MgSO 4 ; 0.42 NaHCO 3 ; pH 5 7.2) containing Methylene Blue (Sigma, St. Louis, MO; 0.003%) and PenStrep (Sigma; 10 mL L 21 ) until required for experiments.…”
Section: Preparationmentioning
confidence: 99%
“…Total RNA (2ng/µl) from such replicates was used for cDNA synthesis using Superscript III reverse transcription kit according to manufacturer’s protocol (Invitrogen, USA). Absolute copy numbers were obtained by droplet digital PCR (ddPCR) using Evagreen mastermix (Biorad, USA) and gene-specific primers that were previously described for zebrafish genes[66] ( camk2a, camk2b1, camk2b2, camk2d1, camk2d2, camk2g1, camk2g2 , and a reference control ef1 α). Absolute quantification in the form of number of copies per μL for each camk2 isoform was normalized with the control ef1 α copy numbers in each replicate.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that the expression of BDNF is regulated by CaMKII α/CREB/BDNF pathway (Tang et al, 2019). Calcium/ calmodulin-dependent protein kinase 2 (CaMKII) is a protein associated with synaptogenesis and neural development, which exists in synapses and is rich in content (Roy, Ferdous, & Ali, 2015). The transcription factor cAMP response element-binding protein (CREB) is involved in the memory process and is also an important target for the treatment of depression (Carlezon Jr., Duman, & Nestler, 2005).…”
Section: Antidepressant Effect On Depressionmentioning
confidence: 99%